Epidemiological aspects and clinical diagnosis of magnesium deficiency in Buffaloes north of Basrah, Iraq (Indian Journal of Animal Production and Management, 2025)
Magnesium is an essential mineral that plays a central role in numerous enzymatic  reactions, neuromuscular function, and energy metabolism. Deficiency of magnesium  in ruminants is often underdiagnosed due to the absence of pathognomonic signs,  yet it may substantially impair productivity and health. In the Basrah region  of southern Iraq, buffaloes represent a vital livestock resource, and subclinical  nutritional imbalances may negatively affect their performance. The present  investigation was managed to investigate the epidemiological aspects, biochemical  alterations, and clinical manifestations related to magnesium deficiency in buffaloes  located north of Basrah. A total of 112 buffaloes were examined through clinical  evaluation and laboratory analysis. Serum concentrations of magnesium, calcium,  phosphorus, sodium, potassium, alkaline phosphatase, total protein, and albumin  were measured. Environmental parameters, containing ambient temperature,  humidity, and wind speed, were also recorded to evaluate their potential contribution  to deficiency risk. Results demonstrated that affected buffaloes exhibited markedly  lower serum magnesium concentrations (0.52 ± 0.01 mmol/L) compared with  healthy controls (1.03 ± 0.02 mmol/L; p < 0.05). Clinically, deficient animals  presented with loss of appetite, restlessness, progressive emaciation, teeth grinding,  muscular tremors, and generalized weakness. Biochemically, magnesium deficiency  was strongly related to reduced serum calcium and sodium levels, while potassium  was meaningfully elevated. Seasonal variations also influenced magnesium status,  with the lowest mean concentrations recorded through December (0.44 ± 0.056  mmol/L), coinciding with adverse climatic conditions. These results propose that  nutritional imbalances, compounded by environmental stressors, may predispose  buffaloes in Basrah to hypomagnesemia. In conclusion, magnesium deficiency  represents an underrecognized metabolic disorder in buffaloes raised under the  ecological conditions of southern Iraq. Regular monitoring of mineral status, along  with improved nutritional management strategies, is recommended to reduce the  incidence of deficiency and enhance overall buffalo productivity.
Keywords: buffalo; magnesium deficiency; epidemiology; Basrah; biochemical profile